2019
DOI: 10.1002/chem.201901259
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY Dyes Bearing Multibranched Fluorinated Chains: Synthesis, Structural, and Spectroscopic Studies

Abstract: A small series of boron‐dipyrromethene (BODIPY) dyes, characterized by the presence of multibranched fluorinated residues, were designed and synthesized. The dyes differ in both the position (para‐perfluoroalkoxy‐substituted phenyl ring or boron functionalization) and number of magnetically equivalent fluorine atoms (27 or 54 fluorine atoms per molecule). Photophysical and crystallographic characterization of the synthesized BODIPYs was carried out to evaluate the effect of the presence of highly fluorinated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Martinez Espinoza et al studied the synthesis and effects of branched fluorinated chains off a BODIPY scaffold [ 21 ]. The synthetic design focused on the fluorinated chain placement in two different positions.…”
Section: Fluorinated Bodipy Dyesmentioning
confidence: 99%
See 3 more Smart Citations
“…Martinez Espinoza et al studied the synthesis and effects of branched fluorinated chains off a BODIPY scaffold [ 21 ]. The synthetic design focused on the fluorinated chain placement in two different positions.…”
Section: Fluorinated Bodipy Dyesmentioning
confidence: 99%
“…The other placement was a substitution of fluorine atoms at the boron center with alkoxy groups containing the fluorinated chain as seen in compounds 4 and 5 ( Figure 3 ) [ 21 ]. In these dyes, an iodination step occurs to add iodine atoms to the BODIPY core to promote singlet oxygen generation.…”
Section: Fluorinated Bodipy Dyesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the design of efficient supramolecular architectures with highly complex structures, such as BODIPY, presents a great challenge and requires comprehensive knowledge of noncovalent interactions. Recently, a few studies have reported observation of the XB interaction in their BODIPY structures [28–31] …”
Section: Figurementioning
confidence: 99%